Supervising Child Protection Practice: What Works? : An Evidence Informed Approach - McPherson, Lynne; MacNamara, Noel (SpringerBriefs in Well-Being and Quality of Life Research,, 2017)
This book presents a model of supervision that is based on both contemporary theory and research, which is strongly contextualized to child and family social work. It draws directly from analysis of in-depth interviews with experienced and post graduate qualified supervisors and supervisees about 'what works' in supervision. These findings bring 'news of difference' in relation to social work supervision offering hope, inspiration and a contemporary model of supervisory practice.